2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6609809
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-compliant neural probes are subject to fluid forces during dissolution of polymer delivery vehicles

Abstract: Ultra-compliant neural probes implanted into tissue using a molded, biodissolvable sodium carboxymethyl cellulose (Na-CMC)-saccharide composite needle delivery vehicle are subjected to fluid-structure interactions that can displace the recording site of the probe with respect to its designed implant location. We applied particle velocimetry to analyze the behavior of ultra-compliant structures under different implantation conditions for a range of CMC-based materials and identified a fluid management protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…To overcome this limitation, ultra-thin or ultra-compliant probes have been demonstrated to minimize how much tissue displacement and local stress affect neural tissue by employing thread- or mesh-like ultrathin structures of polymer materials [ 215 ]. This category of neural probes includes ultrathin and open mesh structures [ 169 , 170 , 171 , 172 , 173 , 174 ], ultra-flexible nano-scale thread structures with a subcellular cross-sectional area [ 175 , 176 ], thin shaft structures embedded in a bio-dissolvable needle [ 177 ], and sinusoidal structures to reduce the tethering force [ 178 , 179 , 180 , 181 ].…”
Section: Non-conventional Neural Probesmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome this limitation, ultra-thin or ultra-compliant probes have been demonstrated to minimize how much tissue displacement and local stress affect neural tissue by employing thread- or mesh-like ultrathin structures of polymer materials [ 215 ]. This category of neural probes includes ultrathin and open mesh structures [ 169 , 170 , 171 , 172 , 173 , 174 ], ultra-flexible nano-scale thread structures with a subcellular cross-sectional area [ 175 , 176 ], thin shaft structures embedded in a bio-dissolvable needle [ 177 ], and sinusoidal structures to reduce the tethering force [ 178 , 179 , 180 , 181 ].…”
Section: Non-conventional Neural Probesmentioning
confidence: 99%
“…Other common approaches for reducing glial scarring involve the use of flexible polymer-based probes with minimized cross-sectional areas, temporarily strengthened by biodegradable supporting materials during insertion [ 178 , 179 , 180 , 181 ]. A typical substrate material is parylene or polyimide, forming a highly conformable probe shank with a cross-section in the range of 2.7–20 μm by 10–35 μm [ 177 , 178 , 179 ].…”
Section: Non-conventional Neural Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…Side effects, however, may exist as these carriers increase the surface area of the shank, evoking greater tissue damage. Dissolvable insertion shuttles might also subject their cargo to substantial fluid forces (Rakuman et al, 2013). In addition, flexible electrodes that are insertion-guided by carriers will need to consider the long-term effects of the carrier need to be considered in order to accurately examine the performance of flexible substrate material itself.…”
Section: Mechanical Approachesmentioning
confidence: 99%
“…Using composite materials, Kozai et al showed that ultrasmall devices may exhibit a “stealth-like” property in the tissue (Kozai et al, 2012). Meanwhile, other devices that adapt their mechanical properties post-insertion should allow for sufficient strength for penetration of the pia mater, but a relaxation of stiffness after a certain period of time (Rakuman et al, 2013; Ware et al, 2014; Harris et al, 2011a, 2011b). Finally, advancements in micro- and nano-printing technologies will provide the ability to tailor the mitigation strategy to the spatially-patterned tissue response (Woolley et al, 2013c).…”
Section: Summary: Challenges and Future Directionsmentioning
confidence: 99%